Comparative analysis of design management procedures in manufacturing and architecture - Fanie Buys; Xabiso Sidloyi (Acta Structilia, 2008)
Design changes due to lack of constructability, cost overruns, delays and dissatisfied clients are but a few of the problems experienced in construction on the account of the poor management of the design processes. This research was conducted to determine the adequacy of design management processes used by Eastern Cape (EC) architectural practices and compare these with the design management processes used in manufacturing in order to establish practices, theories, principles, technologies and deliverables that can be transferred from the manufacturing into the construction industry to improve efficiency of architectural design management. A questionnaire was designed to acquire primary, factual and attitudinal data from EC architectural practices while secondary data were acquired through a literature review. The main findings were that design management processes, continuous improvement philosophies, lean principles, and Information and Communication Technology (ICT) used by EC architectural practices are not similar to those used in manufacturing. Therefore EC architectural practices could increase their efficiency by adopting some of the design management processes, ICT, continuous improvement philosophies and lean principles originating from the manufacturing industry.